ChemInform Abstract: Organoiron‐Mediated Synthesis and Redox Activity of Organoiron‐Containing Dendrimers. Issue 13 (March 2015) - Astruc, Didier; Wang, Yanlan; Rapakousiou, Amalia; Diallo, Abdou; Djeda, Rodrigue; Ruiz, Jaime; Ornelas, Catia
Abstract Review: 88 refs.